2005
DOI: 10.1179/037195505x28519
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and utilization of iron and carbon values from blast furnace flue dust

Abstract: Waste recycling in an integrated iron and steel plant is important with regard to environmental and economic considerations. However, recycling of the waste needs to be supported by metallurgical studies to reap the maximum economic benefit. In this article, a typical flue dust sample obtained from an Egyptian iron and steel company was characterised and the amenability of recovering iron and carbon values from it was investigated. Flotation was used to recover carbon values while magnetic separation was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The Egyptian Iron and Steel Company generates a great deal of blast furnace flue dust (20000-30000 t year −1 ), a typical analysis of which shows that it contains 33·30% carbon and 27·20% Fe as estimated by Ahmed Yehia et al [26].…”
Section: Introductionmentioning
confidence: 99%
“…The Egyptian Iron and Steel Company generates a great deal of blast furnace flue dust (20000-30000 t year −1 ), a typical analysis of which shows that it contains 33·30% carbon and 27·20% Fe as estimated by Ahmed Yehia et al [26].…”
Section: Introductionmentioning
confidence: 99%
“…The major part of flue dust consisted of Ͻ0.5 mm particles and more than 85% was in the size range Ͻ0.250 mm. This shows that the upper particle size range of investigated flue dust samples in this study corresponded in magnitude 6,7) to samples collected from production blast furnaces. However, it is important to point out that the quality of raw material used and raw material handling before charging influences off-gas dust in different blast furnaces along with the different gas-cleaning equipment for separation of flue dust and sludge.…”
Section: Discussionmentioning
confidence: 84%
“…Characterization of flue dust from an Egyptian iron and steel company showed that about 74 wt% of the material was below a particle size of 210 mm. 6) Chemical analysis showed that carbon was found in the coarser sizes above 210 mm and iron in the finer sizes below 210 mm. Determination of particle size of flue dust from an Iranian blast furnace showed that almost all of the material was in the size range Ͻ210 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The main constituents of the BF dedusting residues, Fe, C and Ca are of some value, which supports recycling, e.g. via the sinter plant [5,6]. However, some tramp elements, particularly Zn, are limited in the recycling stream, as they can cause operational problems in the BF.…”
Section: Introductionmentioning
confidence: 99%